INCREASING VOCABULARY OF VIII GRADE STUDENTS AT SMPN 3 OGODEIDE THROUGH WORD GAME - Indrawati, Inda (Universitas Madako Tolitoli, 2017)
The objective of this research is to identify whether the use of word game can increase students’ vocabulary. An experimental design is use to collect the data, while quantitative approach is use to analyze them. The research takes by the VIII grade of SMP Negeri3 Ogodeide. It is conduct in one class (VIIIA). The data are obtained through a pre-test and post-test. The researcher used SPSS 16.0 program to analyze the data collection. The pre-test is use to measure the students’ previous in vocabulary, the treatments are applying materials through word game, and the post-test is use to find out the students’ vocabulary ability after given treatments. The results of this research show that word games can effectively increase students’ vocabulary. The improvement can be seen in the form of students’ behavior and students’ score. The students become more active in teaching and learning process. The improvement of students’ score can be seen from the differences between pre-test and post-test. The mean score of pretest is 23.76 and it improves to 75.29 in post. Moreover the Minimum Mastery Criterion of English lesson was 70 (seventy). Then the data of both tests are analyzed by using T-test, and the result showed that the T-test value 24.51 is greater than T-table value 2.131. It can be inferred that word game is very effective to increase students’ ability in vocabulary. From the test result, it shows that there is a significant improvement of students’ vocabulary after the researcher conducts the research. It proves that teaching vocabulary through word game can increase students’ vocabulary. Key words: Increasing, vocabulary, word game.